Evaluasi Fitur dan Potensi Aplikasi Qanda sebagai Media Belajar Mandiri Matematika untuk Siswa Sekolah Dasar - Anisa Jahro Pandiangan; Alvina Khairunisa; Tasya Azra Zulaikha Siregar; Syahrial Syahrial (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of digital technology has brought significant changes to education, encouraging more interactive and independent learning approaches. Artificial intelligence (AI)-based learning applications like Qanda have emerged as one solution to help elementary school students learn independently, especially in mathematics, which is often considered a difficult subject. Qanda offers features such as scanning math problems with OCR technology, a learning community for collaboration, Indonesian language support, a formula calculator, and daily quizzes. Evaluations of Qanda demonstrate its potential as an independent learning medium that is friendly for elementary school students. This research uses a qualitative method with literature studies and analysis of user reviews of the application.